1999
DOI: 10.1093/geront/39.3.310
|View full text |Cite
|
Sign up to set email alerts
|

English Language Proficiency Among Older Hispanics in the United States

Abstract: Hispanics will constitute a growing part of the older population well into the 21st century. Accompanying this growth, we can expect that challenges associated with a large bilingual and non-English speaking older population may become more pronounced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…As the majority of our study sample resided in high Hispanic-density neighborhoods, language acculturation may not have been essential to manage day-today activities. Generally low levels of education and limited economic resources may have further hindered motivation and accessibility to learning English, as previously reported for older US Hispanics (12). US Census Bureau data confirm that Puerto Rican and Mexican immigrants have lower rates of language shift to English than other Hispanic immigrant groups (58).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…As the majority of our study sample resided in high Hispanic-density neighborhoods, language acculturation may not have been essential to manage day-today activities. Generally low levels of education and limited economic resources may have further hindered motivation and accessibility to learning English, as previously reported for older US Hispanics (12). US Census Bureau data confirm that Puerto Rican and Mexican immigrants have lower rates of language shift to English than other Hispanic immigrant groups (58).…”
Section: Discussionmentioning
confidence: 67%
“…Thus, of the commonly-used proxy measures of acculturation, language use may be the most sensitive measure (55) because it is associated with many other factors – it affects the way an individual interacts with society (12), one’s understanding of different cultures, one’s self-management of health conditions by more easily understanding and incorporating health care providers’ recommendations (59), and knowledge and understanding of available healthful foods and dietary trends. Indeed, national survey findings indicate that limited English-proficient Hispanics were less likely than those with more proficiency to report receiving advice on physical activity and/or diet (59).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although no published research has examined this issue directly, indirect evidence may be available to support such a conclusion. For example, Mutchler and Brallier (1999) found that older Hispanics in the United States, particularly those living in Hispanic enclaves, tend to have poor English proficiency despite residing in the United States for many years. As a result, for individuals who immigrate as adults to enclave contexts, increasing length of residence in the receiving culture may not correspond to increasing endorsement of receiving-culture practices.…”
mentioning
confidence: 99%